Factors associated with concurrent sexual partnerships in four provinces, South Africa-2008 - Elhassan, Muntasir Mohammed Osman (My University, 2014)
Concurrent sexual partnerships are a sexual network pattern that speeds the spread of HIV/AIDS and Sexual Transmitted Infections(1). Multiple and concurrent Sexual Partnerships (MCP) are part of behavioural drivers and are playing main role in the increase of HIV incidence(2). The main aim of the study is to identify the possible socio-demographic and behavioural factors that are associated with concurrent sexual partnership in 4 communities of South Africa(SA), so as to inform HIV prevention programmes in designing targeted interventions for addressing this problem in specific communities. The ultimate goal is to reduce the incidence of new HIV infections
Research report submitted in partial fulfilment for MSc (Med) in Epidemiology and Biostatistics in the School of Public Health, 2013
Keywords: HIV Infections--epidemiology--South Africa; HIV--prevention & control--South Africa--Statistics; Sexual Behavior--statistics & numerical data--South Africa